STD Training in Canadian Medical Schools - Jo-Anne A Doherty; A Gordon Jessamine (Canadian Journal of Infectious Diseases)
OBJECTIVE: The emergence of the acquired immune deficiency syndrome in 1981 and the consequent publicity surrounding sexual behaviour has increased the likelihood that patients will seek medical advice. Sexually transmitted disease (STD) teaching and postgraduate medical programs in Canadian schools of medicine have not been adequately documented. Accordingly, the Laboratory Centre for Disease Control. Department of National Health and Welfare, sought to determine the magnitude and scope of STD training in these schools. DESIGN: A four page questionnaire sought information on preclinical, clinical and residency training in terms of the number of classroom and laboratory hours of instruction, the subspecialty responsible for providing the training, and the clinical ‘hands on’ experience of the teachers: each respondent was also asked to assess the quality and scope of instruction provided at his/her medical school. SETTING/PARTICIPANTS: The questionnaire was mailed to the Dean of each of the 16 schools of medicine in Canada: it was requested that the questionnaire be forwarded to and completed by the person responsible for STD training at the university. RESULTS: Thirteen schools (81%) completed the questionnaire. Each school indicated that some STD instruction was provided at the undergraduate level: the mean number of hours of classroom instruction was 6.1. Physicians with STD clinical ‘hands on’ experience were responsible for teaching in 12 schools. Infectious disease residents spent 4 to 80 h on STDs, while those from other residency programs where STD was not an elective spent 2 to 8 h. Each medical school was asked to provide an evaluation of its program. Only three respondents considered their STD training program adequate. The majority of schools responded that infectious disease residents received sufficient training but the training offered medical students and residents in other programs was less than adequate. The quality of teaching was considered ‘excellent’ in three schools, ‘good’ in nine, and ‘poorly co-ordinated’ in one. CONCLUSIONS: There is no simple solution to ensure that every physician in Canada receives sufficient clinical training in STDs. Collaborative and cooperative efforts by federal, provincial and local governments, professional societies, licensing bodies, medical schools, residency programs, STD clinical directors and provincial and territorial directors of STD control, should be encouraged.